Core needle biopsy for diagnosing lymphoma in cervical lymphadenopathy: Meta‐analysis. Issue 10 (4th August 2020) - Warshavsky, Anton; Rosen, Roni; Perry, Chava; Muhanna, Nidal; Ungar, Omer J.; Carmel‐Neiderman, Narin Nard; Fliss, Dan M.; Horowitz, Gilad
Abstract: Background: The diagnostic yield of core needle biopsies (CNB) in cervical lymphadenopathy for lymphoma diagnosis is controversial. The aim of this study was to calculate the accuracy of cervical CNB in diagnosing lymphoma. Methods: We conducted a meta‐analysis of all studies on patients presenting with cervical lymphadenopathy and referred to CNB. Patients with a diagnosis other than lymphoma were excluded. All cases diagnosed with lymphoma sufficient to guide treatment based on CNB outcome were considered accurate (actionable) results. A separate meta‐analysis was performed for various lymphoma subtypes. Results: Three prospective and 19 retrospective studies, comprising 1120 patients, met the inclusion criteria. The rate of actionable lymphoma diagnoses following CNB ranged from 30% to 96.3%, with a random‐effects model of 82.45% (95% confidence interval [CI] =0.76‐0.88) and a fixed‐effects model of 78.3% (95% CI =0.75‐0.80). Conclusion: CNB for cervical lymphadenopathy in lymphoma cases is relatively accurate in guiding treatment.